Keanekaragaman dan Pola Penyebaran Makrozoobentos di Sungai Pondo dan Pemanfaatannya sebagai Sumber Belajar - Ayu Rifka Ramadani; Fatmah Dhafir; Masrianih Masrianih; Syech Zainal (Universitas Tadulako, 2021)
The Pondo River is one of the rivers in Central Sulawesi which crosses the Poboya, Lasoani, Tanamodindi and Talise villages. Administratively, it is located in Mantikulore District, Poboya Village. This study aims to determine the level of diversity and distribution patterns of macrozoobenthos in the Pondo River and its use as a learning resource. This research is a descriptive study that uses a random sampling method, with surbernet as a means of taking samples. To determine the level of diversity using the Shannon-Winner diversity index formula, to determine the distribution pattern using the Morista distribution index. The results showed the diversity of macrozoobenthos in the Pondo River, namely: H '= 1.36 moderate diversity. The distribution pattern of macrozoobenthos, namely: The pattern of distribution in groups (clustered) and uniform (regular), of the 10 macrozoobenthos found in the species Hydropsyche sp. has a clustered distribution pattern (clustered). Based on the results of the validation test, this research is suitable to be used as a learning resource in the form of a pocket book with a feasibility percentage of 82.1%.